THE FEATURES OF POST-GRADUATE DENTAL TRAINING AT THE DEPARTMENT OF POSTGRADUATE EDUCATION OF DENTISTS OF THE UKRAINIAN MEDICAL STOMATOLOGICAL ACADEMY - K. Udaltsova-Hrodzynska; O. Pisarenko (Український стоматологічний альманах)
According to the requirements, the postgraduate education departments for dentists should be the first to adjust their programs and equipment to technological progress in the branch. During the last two decades the department solved issues of optimal implementation of each technology in the educational process.